Serial Fu Manchu : The Chinese Supervillain and the Spread of Yellow Peril Ideology - Mayer, Ruth, 1965- (Book collections on Project MUSE., 2014)
The evil mastermind--and master of disguise--Fu Manchu has long threatened to take over the world. In the past century, his dastardly plans have driven serialized novels, comic books, films, and TV. Yet this sinister Oriental character represents more than an invincible criminal in pop culture; Fu Manchu became the embodiment of the Yellow Peril. Serial Fu Manchu provides a savvy cultural, historical, and media-based analysis that shows how Fu Manchu's irrepressibility gives shape to--and reinforces--the persistent Yellow Peril myth. Ruth Mayer argues that seriality is not merely a commercial strategy but essential to the spread of European and American fears of Asian expansion. Tracing Fu Manchu through transnational serials in varied media from 1913 to the 1970s, Mayer shows how the icon evolved. She pays particular attention to the figure's literary foundations, the impact of media changes on his dissemination, and his legacy.